Thrombophilic Risk of Factor V Leiden, Prothrombin G20210A, MTHFR, and Calreticulin Mutations in Essential Thrombocythemia Egyptian Patients - Mohamed S. El-Ghonemy; Solafa El Sharawy; Maryan Waheeb Fahmi; Shaimaa El-Ashwah; May Denewer; MA El-Baiomy (Advances in Hematology)
Objectives. Essential thrombocythemia (ET) is one of the myeloproliferative neoplasms characterized by a sustained elevation of platelet numbers with a tendency for thrombosis and hemorrhage. The aim of this work is to establish the relation between calreticulin, factor V Leiden, prothrombin G20210A, and MTHFR mutations in ET patients and the thrombotic risk of these patients. Methods. This study was carried out on 120 ET patients and 40 apparently healthy individuals as a control group. Results. There were increases in WBCs, PLT counts, PT, fibrinogen concentration factor V Leiden, and MTHFR mutation in ET patients as compared to the control group (P<0.05). Also, there were increases in WBCs, PLT counts, and hematocrit value in thrombosed ET patients as compared to the nonthrombosed ones (P<0.05). On the contrary, there was no significantly statistical difference in ET patients with JAK2 V617F positive mutation versus the JAK2 negative group (P>0.05) and in patients with cardiovascular risk factors versus patients with noncardiovascular risk factors (P>0.05). ET patients with factor V Leiden, prothrombin gene, and CALR mutations were more prone to thrombosis (odds ratio 5.6, 5.7 and 4.7, respectively). On the contrary, JAk2V 617F and MTHFR mutations have no effect on the thrombotic state of those patients. Conclusion. There is a significant increase risk of thrombosis in ET patients with CALR mutation, thrombophilic mutations, as well as factor V Leiden and prothrombin gene mutation with a risk of developing leukemic transformation.